PROSES TEKNOLOGI PEMBUATAN MESIN PEMIPIH KOLANG KALING MODEL DRUM ROTARI KAPASITAS 40 KG/JAM - Pranata, Edi; Mahadi, Batu (MEKANIK: Jurnal Ilmiah Teknik Mesin, 2019)
The process of making a propeller flakes machine uses a rotary drum with a capacity of 40 kg / hour, has a construction machine consisting of, pressing mechanism, flaking and scraping mechanism. Scaffolding mechanism that uses supporting components such as elect romotor, gears, reducers, chains and bearings. In the making of the skeletal flakes machine aims to determine / choose the type of tooling equipment suitable for use, determine the process of making machines, the time needed to do both component and assembly work and the feasibility of testing the tool. fro quickly. from the results of making machines obtained overall machining time of 464.7 (minutes) or 7.7 hours If the efficiency of this machine work is estimated at 75% or (0.75), then the time to work on this machine becomes 7.7: 0.75 = 10.3 hours.